Study of the Application of Environmentally Friendly Concepts in Micro and Small Businesses - Atika Aini Nasution; Yasuli Bindulem; Zahara Meutia (International Journal of Advanced Research, 2024)
This study aims to analyze the application of environmentally friendly concepts in micro-enterprises and understand the factors that influence the implementation of these sustainable practices. Amidst increasing global awareness of environmental issues, micro-enterprises have an important role in supporting sustainable development through more responsible business practices. The research method used is a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and literature studies. The research sample consists of several micro-enterprises in the production and service sectors in certain areas that have begun to implement environmentally friendly concepts in their business operations. The results of the study indicate that some micro-entrepreneurs have adopted environmentally friendly practices such as the use of environmentally friendly raw materials, waste management, energy efficiency, and the use of simple technology. However, the implementation of this concept still faces several obstacles, including limited capital, access to environmentally friendly technology, and lack of knowledge and socialization about the long-term benefits of these practices. Factors such as government support, incentive policies, and ongoing assistance are considered important drivers for the successful implementation of environmentally friendly concepts.